Quadratic Polynomial-Based APSD PWM Technique for Dual Three-Phase Inverters - Wiryajati, I Ketut; Wahyu Satiawan; I Made Budi Suksmadana; Ida Bagus Fery Citarsa; Supriono (Indonesian Journal Publisher, 2025)
Three-phase inverters are widely used in industrial applications, including motor drives, renewable energy systems, and electric vehicles. One significant issue in these systems is harmonic distortion, which lowers power efficiency and degrades output voltage quality. To address this, the study proposes a quadratic polynomial fitting technique to optimize Pulse Width Modulation (PWM) signals, aiming to reduce harmonics and improve power quality. This research focuses on a dual three-phase inverter configuration, which provides better current distribution, reduced power losses, and increased resilience to electrical disturbances. The use of quadratic polynomial fitting allows for more precise PWM waveform generation, resulting in lower Total Harmonic Distortion (THDi). The methodology involves mathematical modeling, simulation using MATLAB/Simulink, and experimental validation with a prototype inverter. Results indicate that the technique significantly reduces THDi, especially at optimal modulation indices. Additionally, implementing an LC filter further improves harmonic suppression, producing a cleaner and more stable output. This approach enhances power conversion performance and is highly suitable for industrial and renewable energy applications where efficiency and power quality are critical